Pengaruh Bystander Effect, Efektivitas Pengendalian Internal dan Tekanan Finansial Terhadap Kecenderungan Kecurangan Akuntansi Pada Lembaga Perkreditan Desa - Ni Wayan Widiantari; I Wayan Sudiana (UNHI Press, 2023)
An act of violating the law that is carried out intentionally to gain personal gain and harm many people is often referred to as a tendency to fraud. The tendency of fraud that continues to be allowed will cause losses for the company to bankruptcy. With this in mind, this study was conducted to analyze the relationship between the bystander effect, internal control effectiveness, and financial pressure on the propensity for accounting fraud. Employees at LPD LPD in Penebel District were used as a population with a research sample of 163 respondents. This study uses multiple linear regression analysis techniques which then produce data showing that the bystander effect and increasing financial pressure will make the tendency of fraud to be higher. The effectiveness of good internal control will reduce the level of tendency to fraud.